Typhoid Fever Risk Factors and Challenges to Control: Narrative Review of The Scientific Literatures - Abdullahi Tawfiq, Umar; Muhammad Mofio, Bintu; Abubakar Jauro, Hadiza; Saleh, Nusaiba; Ahmad Muhammad, Mubarak (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Typhoid has remained endemic in parts of Asia and Africa, where the morbidity and mortality are high. It is believed that among the factors responsible, lack of knowledge on risk factors and control challenges are important. Hence, the objective of this article was to generate a non-systematic narrative review on typhoid risk factors and control challenges which can be understood by majority of the stakeholders. Data sources used included reviews and original articles available from 1997 to 2019, from PubMed, Google Scholar, JSTOR, and Sciencedirect. 76 publications were included, and 20 risk factors and 6 control challenges were outlined. Some of the risk factors included contaminated water, contaminated food, contact with a typhoid carrier, contact with a typhoid patient, lack of proper handwashing, lack of vaccination, hot weather, and mechanical vectors, while some of the control challenges included increase in drug resistance, data unavailability, and vaccine limitations. Findings indicated that though typhoid is transmitted through the faeco-oral route, a number of risk factors play important roles in its transmission, and these factors are common in many regions of the world especially in developing and underdeveloped countries. Also, understanding the control challenges will guide provision of more efficient health interventions.